Adiponectin and intracardiac haemodynamics state in hypertensive overweight patients - N. I. Petrik (Сучасні медичні технології)
Investigation of adiponectin levels andintracardiac haemodynamic statehas been done in 96 patients divided into two groups (1st group – 64 hypertensive (stage II) overweight patients, medium age 59,0 (48,0–63,0) years; 2-nd group – 32 hypertensive (stage II) patients, medium age 58,0 (53,0–63,0) years, normal weight). Dependences between the left auricle size, blood pressure, and BMI increase, as well as between the left ventricle remodelling character and BMI in the surveyed patients were uncovered. Theconcentric left ventricle hypertrophy observed in the surveyed patients was characterised by normal contractility, leftventricle posteriorwall relative thickness increase, and normal or reduced end-diastolic volume. The blood serum adiponectin level in hypertensive (stage ІІ) overweight patients was significantly (nearly 3 times) lower as compared to the group of hypertensive (stage ІІ) patients who had normal weight.